Prevalence of hypertension in adult population and adherence to treatment among hypertensives in an urban area - Gudipally Monica; Praveena Ganapa (National Board of Examinations Journal of Medical Sciences, 2024)
Introduction / background: Hypertension is one of the most common non-communicable diseases and is an important public health problem around the world. Poor adherence to anti-hypertensive medication is one of the biggest challenges in the control of hypertension. Study was undertaken with the aim to study the prevalence of hypertension and adherence to treatment among hypertensives in our study area. Methodology: A community based cross-sectional study was conducted using systemic random sampling among 560 individuals (aged >= 30years). Informed Consent was taken from all the study subjects, WHO STEPS questionnaire was used for prevalence and MMAS-8 was used for adherence. Chi square test/t-test and regression were applied to determine association between various risk factors and level of adherence. Results: The present study concluded that 27.9% of the study population had hypertension. According to MMAS-8 scale the level of adherence among the participants with hypertension after ruling out the newly diagnosed hypertensive from the total hypertensive was high in 77 (57%), moderate in 29 (21.5%) and low in 29 (21.5%) Forgetfulness was the most common (21.9%) reasons for the poor adherence. On multivariate regression age <50 years and non-working status showed statistically significance with level of adherence with odds of 3.61 (1.29-10.13) and 3.296 (1.16-9.36) respectively. Conclusions: The population under investigation had a moderate level of medication adherence. Enhancing the study population's literacy could help overcome these obstacles, and actions need be taken to ensure that behaviour modification and health education are communicated effectively.